Clinical Assessments of Balance in Adults with Concussion: An Update - Murray, Nicholas G.; Reed-Jones, Rebecca J.; Szekely, Brian J.; Powell, Douglas W. (Seminars in Speech and Language, 2019)
Postural instability is a cardinal indicator of concussion. Assessments of the postural control system range from clinical to laboratory tests that assess the balance of the individual. In a previous article regarding clinical assessment of balance in adults with concussion, we reviewed the importance of balance as a component in concussion evaluations. The purpose of this review article is to update the information previously published in 2014. Since 2014, research has provided evidence for the incorporation of dynamic methods for evaluating balance postconcussion with particular emphasis on sensory system integration and dual tasking. Therefore, this review will examine the current state of knowledge on how concussion injuries affect postural control, advancements in evaluating balance postconcussion, such as novel eye-tracking techniques, and current recommendations for best practices for balance assessment.
Keywords: balance assessment; postural control; dual task; gait; oculomotor